A dolphin only looks like a fish: Players' behaviour analysis is not enough for game understanding in the light of the systems approach - a response to the reply by McGarry and Franks - Lebed, F. (European Journal of Sport Science, 2007)
this article I defend my previously published system approach to game playing in sports (Lebed, 2006). Founded on the main argument of mine about insufficiency of performance analysis only for games study, it is based on an inter-disciplinary comprehension of sporting game events from four different angles: the logical-philosophical, the behavioural (performance), the anthropological, and complexity angles. The paper consists of four parts, corresponding to the four angles. The first three parts offer deconstructive and reconstructive analysis. The three provide criticism of McGarry and Frank's arguments against my view of complex dynamical systems in sports. The logical analysis negates my opponents' general view of a match (a process) as a dynamical system. The behaviour analysis refutes their claim about couple oscillator dynamics as a universal dynamically interpreted model of game playing. The anthropological panoramic vision of sporting games leads me to conclude that my opponents' analysis of two exclusively interacting sides in a squash or soccer contest is too narrow and insufficient to explain the broad diversity of games. According to the, classification suggested in Lebed (2004), I offer seven possible models that can systematically reflect different groups of games. In the fourth part, the complexity angle is analysed from a constructive point of view. Here I take one of the above seven models and try to outline a ''soccer-like'' game perspective modelling founded on the view of play process as a conflict of two four-level self-regulating complex systems, where each one is additionally involved in its own loop of cybernetic regulation.